1995
DOI: 10.1007/bf01270663
|View full text |Cite
|
Sign up to set email alerts
|

Water balance and resistance to desiccation in rock-dwelling snails

Abstract: We have examined the resistance to desiccation among rock-dwelling land snails of various phylogenetic groups: Cristataria genezarethana (Clausiliidae), Rupestrella rhodia (Chondrinidae) and Levantina caesareana (Helicidae), all from the same location in Israel. L. caesareana was the most resistant and R. rhodia the least resistant to desiccation and C. genezarethana was of intermediate resistance. Differences in the rates of water loss during desiccation were determined mainly by rate of water loss during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
(12 reference statements)
1
15
0
2
Order By: Relevance
“…This is the result of their lower mass (fluid) loss during desiccation. The present findings also show that the osmotic changes in the extra-pallial compartment were larger than expected from total mass (fluid) loss and thus suggest that water is preferentially moved to the soft body tissue, as has been previously suggested by Arad et al (1992Arad et al ( , 1995. In general, the osmolality of this fluid is lower than that of the hemolymph in pulmonate snails (Potts, 1975;Smith, 1981).…”
Section: Downloaded By [Uq Library] At 05:27 20 November 2014supporting
confidence: 83%
“…This is the result of their lower mass (fluid) loss during desiccation. The present findings also show that the osmotic changes in the extra-pallial compartment were larger than expected from total mass (fluid) loss and thus suggest that water is preferentially moved to the soft body tissue, as has been previously suggested by Arad et al (1992Arad et al ( , 1995. In general, the osmolality of this fluid is lower than that of the hemolymph in pulmonate snails (Potts, 1975;Smith, 1981).…”
Section: Downloaded By [Uq Library] At 05:27 20 November 2014supporting
confidence: 83%
“…More globose snails have difficulties in to use fissures, the most protective refuges against dehydration, as shelter, and it is possible that these specimens had a higher risk of dying from desiccation. On the other hand, more flattened snails have a lower body volume, and thus less capacity to store reserves and to survive the periods of aestivation (Arad et al 1995), which can last six months in the study area (unpublished data). Kingsolver et al (2001) found a median value of 0.10 for gradients of non-linear selection, although these values seem to overestimate the true strength of selection (Hersch and Phillips 2004).…”
Section: Discussionmentioning
confidence: 98%
“…4.5% per day) was the highest found so far in our series of studies (Arad, Goldenberg & Heller, 1989, 1992, 1995Arad, 1990Arad, , 1993aArad, Goldenberg, Avivi et al, 1993). Apparently, this snail's rate of water loss (approx.…”
Section: Discussionmentioning
confidence: 48%
“…Morphometric characteristics of four groups of Lauria cylindracea: original group brought from the ®eld and of snails aestivating in the laboratory for 2, 3, and 4 months (June, May, and April, respectively) under condition of full hydration, desiccation, and after aestivation. Our studies of the small-size juvenile and adult Cristataria genezarethana (Clausiliidae) and adult Rupestrella rhodia (Chondrinidae) indicated that snail size alone cannot explain the differences in resistance to desiccation between these two species (Arad, Goldenberg & Heller, 1995). m i, initial fully-hydrated mass; m t, ®nal mass (after desiccation or aestivation); msh, shell mass; mwb, wet soft body mass; mdb, dry soft body mass; shf, shell free.…”
Section: Discussionmentioning
confidence: 84%